55.1k views
2 votes
Solve the system. d = 2 − 6c 1 2 c − c = 1 A) (0, 2) B) (2, 0) C) (0, 0) D) (0, −2)

User Leo Selig
by
5.2k points

2 Answers

0 votes

Answer:

The answer is (0,2) and yes I'm in quarantine

Explanation:

Multiply the first equation by -1/2:

-1/2d - 3c = -1

1/2d - c = 1

-4c = 0

c = 0

d = 2 - 6(0)

d = 2

User FrankMonza
by
4.6k points
4 votes

im sorry i doint have the answer but i am bored

im only 14 so idk this one

are you on qurentene 2?

User Lhaferkamp
by
4.4k points